Palynological Analysis of a Peat Core from Imnavait Creek, the North Slope, Alaska - Eisner, Wendy R. (ARCTIC, 1991)
The pollen record of a 160 cm peat core from Imnavait Creek, a small upland basin in the northern foothills of the Brooks Range, Alaska, reveals a history of vegetation change from the early Holocene to the present. The Alnus rise within the region occurred after 8500 yr B.P. Betula and Cyperaceae are the major floristic elements throughout the diagram, and this, along with the significant levels of Salix and Ericaceae, suggest that the area was characterized by a mosaic of herb and shrub tundra communities, dependent on variations in terrain and moisture availability.Key words: palynology, Peat , North Slope, Alaska, pollen, Brooks Range, vegetation history, Holocene Mots clés: “Paleontologie”, tourbière, pente nord, Alaska, pollen, Brooks Range, histoire de la végétation, holocène